Prevention of Dengue Fever Based on Dominant Risk Factors within Elementary School Environment in Bandung City - Kurniawati, Ratna Dian; Martini, Martini; Wahyuningsih, Nur Endah; Sutiningsih, Dwi; Sutriyawan, Agung (Public Health of Indonesia, 2024)
Background: Dengue fever is an environment-based disease that is endemic in Bandung City. Bandung City with an average temperature of 25.86°C has a humid and cool climate which is a favorable environment for Aedes aegypti. The average amount of rain per day is 21.3 days per month with an average rainfall of 200.4 mm. These environmental conditions favor the breeding of Aedes aegypti. Objective: The study aimed to obtain the dominant variables in the 3M Plus PSN.Penelitian ini merupakan penelitian kuantitatif dengan desain cross sectional. Method: The population in this study were all elementary school students in Bandung City. Through the Cluster Sampling calculation, 973 minimum samples from 13 elementary schools were obtained. With a minimum sample for each elementary school totaling 76 6th-grade students. Results: The results of the study showed that a Knowledge P-value of 0.023, Attitude P-value 0.036, Perception P-value of 0.000, and motivation P-value of 0.018 were associated with DHF Prevention through 3M Plus PSN. Exposure to information media on dengue prevention through the 3M Plus PSN is not associated with dengue prevention through the 3M Plus PSN. The variable that most influenced the prevention of Dengue Fever through the 3M Plus PSN was perception with a P-value of 0.000 CI of 2.118 (1.639-2.737). Conclusion: Knowledge, perception, attitude, and motivation are related to dengue fever prevention through 3M Plus PSN. Perception is the most dominant factor associated with the prevention of dengue fever through the 3M Plus PSN.